The effect of bolus injection of phenylephrine and norepinephrine in preventing hypotension in spinal anesthesia in patients undergoing elective cesarean section: a single-blind clinical trial study - Sepideh Yazdanpanah; Seyede Mahrokh Alinaghimaddah; Mahin Tatari; Arazbardi Ghorchaei; Zolaykha Karamelahi (Mashhad University of Medical Sciences, 2023)
Introduction: Neuraxial analgesia is the most efficient way to relieve pain during delivery. Hypotension is commonly occurred in cesarean surgery. The vasopressors are used as one of the most important methods of prevention and treatment of hypotension. So the present study was performed with aim to determine the effect of bolus norepinephrine and phenylephrine to prevent hypotension in spinal anesthesia in patients undergoing elective caesarean section. Methods: This clinical trial study was conducted in 2022 on 90 pregnant women of 36-41 weeks who were candidates for elective cesarean section without anesthesia restrictions. Immediately after spinal anesthesia, phenylephrine (50 μg/ml) was injected for the first group and norepinephrine (5 μg/ml) for the second group. Vital signs were non-invasively monitored and recorded. Data analysis was done using SPSS statistical software (version 19) and t-test, Man-Whitney U, Chi-square and Fisher's exact tests. P<0.05 was considered statistically significant. Results: The mean systolic blood pressure (p=0.001), diastolic blood pressure (p=0.001) and mean arterial blood pressure (p=0.003) in the norepinephrine group in the first 6 minutes were significantly lower than the phenylephrine group. The heart rate (p=0.001) in the first 6 minutes was significantly higher in the norepinephrine group than the phenylephrine group. Conclusion: Hemodynamic changes following the administration of bolus epinephrine are less compared to phenylephrine. It causes better control of blood pressure and heart rate.